Employment Psychology of Young Migrant Workers During Coronavirus Disease 2019: A Comparative Study Between Construction Workers and Food Delivery Knights - Xue, Cong; Zhou, Chuan; Su, Xing; Qin, Zhongfu (Frontiers in Sociology, 2022)
The Chinese construction industry has been facing labor shortages and aging workforces for years, and the eruption of coronavirus disease 2019 has exacerbated the problem. In the contrast, food deliver industry has grown rapidly during the pandemic with a surge in the number of takeaway riders. It is vitally important to understand the employment psychology of the young migrant workers, the main body of workforce for both industries. The presented study employed three types of data for investigation, including face to face interview, online information from social media, and World Value Survey data. Results showed that construction workers and takeaway riders have different preference on outcome expectations to their jobs, critically affected by their distinction in age, education and family conditions. To be specific, construction workers mainly focus on physical expectations such as money and takeaway riders care more about social expectations like approval and self-evaluation expectations which can affect job satisfaction. As reflected in their job search behavior, construction workers are more willing to be overemployed and takeaway riders pay more attention on working time, environment and autonomy of their jobs